PENGARUH PEMBERIAN KOMPOS JERAMI PADI TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Bayu Dominika Elkas; Tengku Nurhidayah; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aims to study the effect and to obtain the best dose of rice straw compost on the growth of the cocoa seedling. The experiment has been conducted at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru. from July to October 2016. The experimental unit was arranged in a completely randomized design (RAL), consisting of 6 treatments: 0, 25, 50, 75, 100 and 125 g/seedling and replicated 3 times. Each experimental unit consisted of 3 seedlings. Parameters observed were seedling height, stem diameter, number of leaves, leaf area, root volume, the ratio of the canopy and root and dry weight. Data were analyzed statistically using analysis of variance and the mean of each treatment was compared by using Duncan’s New Multiple Range Test at level of 5%. The results showed that the dose of  rice straw compost could improve the seedling height, stem diameter, number of leaves, leaf area, root volume, ratio of the canopy and root and dry weight. The dose of rice straw compost at 125 g/polybag produced the best growth of cocoa seedling. Keywords: cocoa seedling, rice straw compost dose